Early-onset fetal growth restriction treated with the long-acting phosphodiesterase-5 inhibitor tadalafil: a case report. (December 2016) - Sakamoto, Mito; Osato, Kazuhiro; Kubo, Michiko; Nii, Masafumi; Tanaka, Hiroaki; Murabayashi, Nao; Umekawa, Takashi; Kamimoto, Yuki; Ikeda, Tomoaki
Abstract Background Severe early-onset fetal growth restriction occurs in 0.4 % of all pregnancies, and the prognoses of these patients are dismal. Severely growth-restricted fetuses (far below 500 g) are thought to be nonviable. Since there have not been effective treatments for such fetal patients, obstetricians have simply tried to identify the optimal timing for their delivery. There are a few reports suggesting that the phosphodiesterase type 5 inhibitor sildenafil has some limited beneficial effects on fetal growth, but there are no such reports on tadalafil, another derivative phosphodiesterase type 5 inhibitor which has a much longer half-life than sildenafil. Here we present a case in which the administration of tadalafil to the mother revived the arrested growth and severe oligohydramnios of the very prematurely growth-restricted fetus. Case presentation We describe a case of early-onset fetal growth restriction with oligohydramnios in a 41-year-old primigravida Japanese woman who was treated with tadalafil (20-mg tablet daily) from 22 weeks' gestational age. Ten days after the initiation of the tadalafil therapy, the amniotic fluid level rose and the weight of the fetus began to increase. A 1024-g baby boy was delivered by cesarean at 32 weeks' gestation. The z-score for fetal head circumference had increased from −2.2 to −1.2, whereas the z-score of the femur legth was decreased to −4.3, indicating that tadalafil preferentially increased the blood flow to important organs. Conclusions We achieved two positive results by administering tadalafil to the mother carrying a severely growth-restricted fetus with oligohydramnios. First, the z-scores of head circumference and abdominal circumference had at first declined but started to rise after the tadalafil administration. Second, the amniotic fluid, which was emptied before the tadalafil treatment, recovered to normal range with this treatment. Tadalafil administration to mothers could be a promising therapy to reverse severe fetal growth restriction and oligohydramnios.